1997
DOI: 10.1002/(sici)1096-8652(199712)56:4<224::aid-ajh5>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

MDS and AML with trisomy 8 as the sole chromosome aberration show different sex ratios and prognostic profiles: A study of 115 published cases

Abstract: A number of chromosome aberrations occur nonrandomly as the sole aberration in malignant and premalignant hematological disorders. They imply very different prognoses. For most of them the survival consequences have been established. For trisomy 8, which is the most frequent numerical aberration in myeloid disorders, the prognostic implications have not been investigated. In order to clarify survival in patients with trisomy 8 as the sole aberration, the literature was searched for such cases. In 115 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
(7 reference statements)
4
24
0
1
Order By: Relevance
“…An updated database search [9] on isolated trisomy 8 reveals that it is seen in 6.0% and 6.8% of karyotypically abnormal AMLs in women and men, respectively. However, a significantly higher frequency in males (12% versus 8.9%; P<0.05; chi-square test) is found in MDS, in agreement with a previous study by Pedersen [30]. Furthermore, there is a clear-cut impact of age on the incidence of trisomy 8 as a sole change in AML, i.e., it increases with age [29,31].…”
Section: Epidemiologysupporting
confidence: 88%
“…An updated database search [9] on isolated trisomy 8 reveals that it is seen in 6.0% and 6.8% of karyotypically abnormal AMLs in women and men, respectively. However, a significantly higher frequency in males (12% versus 8.9%; P<0.05; chi-square test) is found in MDS, in agreement with a previous study by Pedersen [30]. Furthermore, there is a clear-cut impact of age on the incidence of trisomy 8 as a sole change in AML, i.e., it increases with age [29,31].…”
Section: Epidemiologysupporting
confidence: 88%
“…In our study, the frequency of trisomy 8 was 9%. This result was similar to the other studies (7%-10%) (22). On the other hand, Panani et al (5) reported that the most common anomaly was trisomy 8 (28%).…”
Section: Discussionsupporting
confidence: 91%
“…So far only one literature search has evaluated independent prognostic factors among AML patients with +8 as a sole aberration revealing trisomy 8 clonal size as a potential predictor in a small number of cases. 13 This unclear prognostic situation is accompanied by an unclear therapeutic situation. Conventional consolidation with high-dose cytarabine seems not to cure the disease, and only anecdotal data are available regarding transplantation strategies in small numbers of patients within each single trial.…”
Section: ;11mentioning
confidence: 99%